(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف البحث إلى التعرف على مدى أثر خلق الثقة عند عملاء المصرف التجاري السوري على تحقيق ولائهم له.والتعرف على مدى تأثير التزام المصرف التجاري السوري تجاه العملاء على تحقيق ولاء العملاء له. ومن أجل تحقيق الأهداف اعتمد الباحث على منهجية تتضمن توزيع (110) استبانة وزعت على عينة عشوائية من عملاء فروع المصرف التجاري السوري في محافظة اللاذقية، واستخدام برنامج SPSS للتحليل الإحصائي من خلال حساب معامل بيرسون ومعامل التحديد. وقد توصل الباحث إلى انخفاض مستوى كل من الالتزام وثقة العملاء يرافقه انخفاض ولاء العملاء للمصرف، كما توصلت الدراسة إلى وجود علاقة ذات دلالة معنوية بين كل من الالتزام وولاء العملاء للمصرف، ومن جهة أخرى وجود علاقة ذات دلالة معنوية بين ثقة العملاء وولاء العملاء للمصرف التجاري السوري. The research aims to identify the extent of the impact of the creation of confidence when the Commercial Bank of Syria clients to achieve their loyalty to him. And to identify the extent of the impact of the commitment of the Syrian Commercial Bank to customers to achieve customer loyalty to him. In order to achieve the goals researcher relied on the methodology include distribution (110) questionnaire was distributed to a random sample of the branches of the Syrian Commercial Bank customers in the province of Lattakia, and the use of SPSS statistical software for analysis by calculating the Pearson coefficient and the coefficient of determination. The researcher reached the low level of both the commitment and the confidence of customers, accompanied by lower customer loyalty to the bank, as the study found, and there is a significant correlation between each of the commitment and loyalty of customers of the bank, on the other hand, and there is a significant correlation between customer trust and loyalty of customers Commercial Bank of Syria.